Survey of Learning Interest in Physical Education among Students Who Play Online Games - Pajar Hari Widodo; Iyakrus; Ahmad Richard Victorian (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This research aims: 1. To determine the interest in learning physical education of students who play online games for class X Mechanical Engineering and X Light Vehicle Engineering State Vocational High School 4 Palembang. 2. To determine the intensity of playing online games for students in class X Mechanical Engineering and X Light Vehicle Engineering at State Vocational High School 4 Palembang. The research method used in this research is quantitative descriptive research. Data collection techniques in this research are observation: the ongoing process of physical education learning activities, questionnaires: in the form of statements regarding interest in learning and intensity of playing online games, and documentation: physical education learning activities and school documents. The data analysis technique in this research is descriptive statistics and quantitative analysis by carrying out normality tests, looking for the mean, standard deviation, variance and percentage of data. The results of this research show that the Physical Education Study Interest Survey of Students Who Played Online Games in Class X Mechanical Engineering and Class X Light Vehicle Engineering at State Vocational High School 4 Palembang, namely: The majority of students in Class moderate physical education lessons. Meanwhile, the intensity of playing online games for students in class X Mechanical Engineering and X Light Vehicle Engineering at State Vocational High School 4 Palembang is also in the medium category.